Structure and dynamics of Mycobacterium tuberculosis tyrosyl-tRNA synthetase in complex with SB-219383 inhibitor - Mykuliak, V.V.; Kornelyuk, A. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
Inhibitor SB-219383 and its analogues are a class of potential inhibitors of bacterial tyrosyl-tRNA synthetases. To study the dynamic pharmacophore features, we have performed molecular dynamics simulations of M. tuberculosis tyrosyl-tRNA synthetase in complex with SB-219383 inhibitor. The inhibitor binds to the active center of the enzyme interacting with the region of binding of tyrosine and a phosphate group. SB-219383 does not interact with the catalytic KMSKS loop.